The Expression of Neogene TIGD3 that Derived from DNA Transposons in Colorectal Cancer Cell lines - Ahmed Arnaoty; Hiba. M. Ahmed; Yves Bigot; Thierry Lecomte (Indian Journal of Forensic Medicine & Toxicology, 2022)
DNA transposons are exposed to a molecular domestication process, which results in the formation of neogenes,which may play a role in human genetic instability. TIGD3 (Tigger-derived [TIGD] family of proteins) is one ofthese Neogene, and its role in the human genome is unknown.Aim: The expression of Neogene TIGD3 in colorectal cancer cell lines and its putative function in carcinogenesisare being investigated.Method: The protein expression of the TIGD3 gene was investigated using the western blot method in twelvecolorectal cancer cell lines (HCT116, SW48, LOVO, DLD1) that are microsatellite instable MSI, (SW480, SW620,HT29, LS123, COLO205, T84, SW403, SW1463) that are microsatellite stable MSS, and in healthy colon tissue as acontrol in our study.Results: The expression of the TIGD3 protein was found in all twelve colorectal cancer cell lines, with varyingdegrees of expression and numerous isoforms, which was not found in healthy colon tissue.Conclusion: There may be a link between colorectal cancer evolution or progression and TIGD3 gene expression.